2015
DOI: 10.1016/j.mod.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

α integrin cytoplasmic tails can rescue the loss of Rho-family GTPase signaling in the C. elegans somatic gonad

Abstract: Integrin signaling relies on multiple, distinct pathways to impact a diverse set of cell behaviors. The Rho family of GTPases are well-established downstream signaling partners of integrins that regulate cell shape, polarity, and migration. The nematode C. elegans provides a simple in vivo system for studying both integrins and the Rho family. Our previous work showed that the C. elegans α integrin cytoplasmic tails have tissue-specific functions during development. Here, we use chimeric α integrins to show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous work showed that C. elegans RHO-1 is essential for ovulation and fertility ( Norman et al. , 2005 ; McMullan and Nurrish, 2011 ; Meighan et al. , 2015 ), but its downstream effectors in ovulation have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that C. elegans RHO-1 is essential for ovulation and fertility ( Norman et al. , 2005 ; McMullan and Nurrish, 2011 ; Meighan et al. , 2015 ), but its downstream effectors in ovulation have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…, 2004 ; McMullan and Nurrish, 2011 ; Kovacevic et al. , 2013 ; Meighan et al. , 2015 ; Ono and Ono, 2016 ), which cooperate to increase phosphorylation of the myosin regulatory light chain (p-MRLC) and actomyosin contractility in smooth muscle and nonmuscle cells ( Somlyo and Somlyo, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…In both tissues, RHO-1/RhoA signaling activates Rho-associated kinase, LET-502/ROCK, which phosphorylates and inactivates the myosin-associated phosphatase regulatory subunit MEL-11 (referred to here as myosin phosphatase), leading to increased p-MRLC ( Wissmann et al. , 1999 ; McMullan and Nurrish, 2011 ; Meighan et al. , 2015 ; Ono and Ono, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…RhoA signaling pathways (Clandinin et al, 1998;Wissmann et al, 1999b;Bui and Sternberg, 2002;Kariya et al, 2004b;Yin et al, 2004;McMullan and Nurrish, 2011;Kovacevic et al, 2013;Meighan et al, 2015;Ono and Ono, 2016a) that cooperate to increase phosphorylation of the myosin regulatory light chain (p-MRLC) and actomyosin contractility in smooth muscle and nonmuscle cells (Somlyo and Somlyo, 2000). In the C. elegans gonad, two phospholipase C isoforms, Cg (PLC-3) and Ce (PLC-1), cleave phosphatidyl inositol to produce inositol 1,4,5triphosphate (IP 3 ), which triggers Ca 2+ release from the endoplasmic reticulum (Clandinin et al, 1998;Bui and Sternberg, 2002;Kariya et al, 2004b;Yin et al, 2004;Kovacevic et al, 2013).…”
Section: Contractions Of Both Sheath and Spermathecal Cells Are Regulmentioning
confidence: 99%
“…This likely increases myosin activity by activating a Ca 2+ -calmodulin dependent myosin light chain kinase (Adelstein, 1982;Somlyo and Somlyo, 2000). In both tissues, RHO-1/RhoA signaling activates Rho-associated kinase, LET-502/ROCK, which phosphorylates and inactivates the myosin-associated phosphatase regulatory subunit, MEL-11 (referred to here as myosin phosphatase), leading to increased p-MRLC (Wissmann et al, 1999b;McMullan and Nurrish, 2011;Meighan et al, 2015;Ono and Ono, 2016a). However, unlike sheath cells, spermathecal cells lack the troponin-tropomyosin complex (Ono and Ono, 2004;Ono et al, 2007) responsible for Ca 2+ regulation of actomyosin contraction in muscle cells (Ebashi, 1984).…”
Section: Contractions Of Both Sheath and Spermathecal Cells Are Regulmentioning
confidence: 99%